KAJIAN REAKTIVASI JALUR LINTAS CABANG DAERAH OPERASIONAL IV (DAOP IV) - Fuadi, Anisi; Egza, Robby Alfadhila; Narayudha, Moga; Kushardjoko, Wahyudi (Jurnal Karya Teknik Sipil, 2014)
The Central Java government was planning to reoperate unused railway, considering the road traffic that was increasing rapidly in Central Java. Today, Central Java region has 663 km of unoperated railway. Most of it was located in the 4th operational region (DAOP IV). This research was planned to make a priority scales about railways which had some potensial to reopen and its properness financially. The activating priority scales which was used in this operation based on analytical demand and analytical supply. Analytical demand consists of the traffic rate and the amount of passenger’s movements at the OD datas. Whereas, analytical supply consists of analytical techniques seen from field conditions such as terrain availability, tools or places conditions, and accessibility. The results shows that unoperated track between Semarang-Demak-Purwodadi-Blora-Cepu has the most potencial to reactivate again for passengers purpose. On the other hand, unoperated track which goes to Tanjung Emas Harbour also become the most potencial track to reactivate considering increasing activities in this harbour. Based on the analytical results, there were two passenger’s scenarios for shifting the use of  train transport, optimisstic scenario and pessimistic scenario. The optimisstic scenario was estimated to had 5058 passengers/day. While, the pessimistic scenario was estimated to had 1759 passengers/day. In order to reactivate the unoperated track between Semarang-Demak-Purwodadi-Blora-Cepu, a new construction was needed. It was because some of the old constructions were vanished and the railway type was very tiny, which were R.25 and R.33 type. All of those things above made this project highly cost, not to mention tools and operational funds to spend for its. From the financial view, the analytical result shows that NPV value was positive, BCR > 1, so it was good enough to reactivated. But, looking at the FIRR results, Semarang-Purwodadi track is the best option, considering its value is 5,69%, while for Semarang-Demak track is only 3,49%, and for Semarang-Cepu track is only 3,47%.  For a better result, reactivation process of this track need to consider surrounding area within the track. Also, it needs better knowledge to understand commodity and region potential in order to raise the incomes.